2021
DOI: 10.2298/vsp190730097a
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vitamin E-coated dialysis membrane on oxidative stress during a single session of on-line hemodiafiltration

Abstract: Background / Aim. Oxidative stress is an important risk factor for the development of cardiovascular atherosclerotic diseases in the population of patients treated with regular hemodialysis. Bioincompatibility of the dialysis membrane and increased concentration of endotoxin in the hemodialysis solution are two main factors that can stimulate oxidative stress. The paper was intended to examine the effect of a vitamin E-coated membrane on oxidative stress during a single session of on-line hemodiafiltration. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
2
3
0
1
Order By: Relevance
“…Our previous research con rmed the fact that patients on hemodialysis are in higher risk for oxidative stress and anemia [33]. Antioxidant potential of SAE, as a speci c formulation, was recently demonstrated in an animal model of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 55%
“…Our previous research con rmed the fact that patients on hemodialysis are in higher risk for oxidative stress and anemia [33]. Antioxidant potential of SAE, as a speci c formulation, was recently demonstrated in an animal model of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 55%
“…The previous studies had shown that selenium, zinc, or L-carnitine supplementation after each HD session for 2-3 months increase the capacity of enzymatic antioxidant protection and the status of malnutrition and decrease the resistance to EPO [ 36 38 ] which accentuate the fact that OS development leads to EPO resistance, as we concluded regarding the results of our study. Moreover, high-flux HD and post-dilution online hemodiafiltration with vitamin E-coated dialysis membranes significantly reduce OS and microinflammation, increase iron availability for erythropoiesis, reduce EPO resistance, and improve nutritional status, quality of life, and the outcome of patients treated with regular dialysis [ 39 41 ], which all together imply role of OS in the development of EPO resistance, as we concluded in our study.…”
Section: Discussionsupporting
confidence: 58%
“…Uremic toxins, altered endothelial function, chronic microinflammation, malnutrition, oxidative stress, resistance to erythropoietin, and anemia are the major non-traditional risk factors for the development of cardiovascular complications in this population [19,20]. Early detection and optimal control of these issues seem to play a key role in preventing cardiovascular co-morbidity in HD patients [21]. In recent years, direct cardiotoxicity of uremic toxins has been increasingly demonstrated, while a reduction in middle molecule retention appears to be independently associated with decreased risk of mortality [22].…”
Section: Discussionmentioning
confidence: 99%